Obeah, Orisa, and Religious Identity in Trinidad, Volume II, Orisa - Stewart, Dianne (Religious Cultures of African and African Diaspora People, 2022)
Dianne M. Stewart analyzes the sacred poetics, religious imagination, and African heritage of Yoruba-Orisa devotees in Trinidad from the mid-nineteenth century to the present.